Analysis of the Station Test Results of the Hungarian Large White and Hungarian Landrace Populations Applying Survival Analysis - Nagy, István; Csató, László; Farkas, János; Radnóczi, László; Vígh, Zsófia (Acta Agraria Debreceniensis, 2002)
Authors analysed the days of fattening in relation to the station test for Hungarian Large White and Hungarian Landrace pig populations using, survival analysis. Survival and hazard functions were calculated in both groups separately for castrates and females. The log-rank test was applied to determine the significance of the differences across the groups. Authors established that within the breeds the functions of the castrates and females were significantly different, namely the castrates reached final weight sooner or, in cases where final weight was not reached by a certain period, castrates reached this weight during the next time unit with a higher probability than the females.